2015
DOI: 10.1121/1.4906158
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of vocal tract model parameters for nasals using sensitivity functions

Abstract: Determining the cross-sectional areas of the vocal tract models from the linear predictive coding or autoregressive-moving-average analysis of speech signals from vowels has been of research interest for several decades now. To tune the shape of the vocal tract to given sets of formant frequencies, iterative methods using sensitivity functions have been developed. In this paper, the idea of sensitivity functions is expanded to a three-tube model used in connection with nasals, and the energy-based sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Consequently, these functions are flexible, and capable of treating any type of resonance, or even anti-resonance. Kreuzer and Kasess [20] also reported that a complex sensitivity function for formants was largely in accord with traditional, physically-derived sensitivity functions.…”
Section: Sensitivity Analysis Between the Cross-sectionalmentioning
confidence: 66%
See 2 more Smart Citations
“…Consequently, these functions are flexible, and capable of treating any type of resonance, or even anti-resonance. Kreuzer and Kasess [20] also reported that a complex sensitivity function for formants was largely in accord with traditional, physically-derived sensitivity functions.…”
Section: Sensitivity Analysis Between the Cross-sectionalmentioning
confidence: 66%
“…To perform sensitivity analysis, a sensitivity function must be newly derived with regard to the peaks of input impedance, because previously reported sensitivity functions [16,17] are related to peaks of the vocal-tract transfer function. To derive a sensitivity function, we used the basic concept of a complex sensitivity function [20]. Unlike the existing sensitivity functions derived from a physical principle [15], complex sensitivity functions are derived formally.…”
Section: Sensitivity Analysis Between the Cross-sectionalmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noted that an alternative to the energy-based approach is to calculate the sensitivity functions with a Jacobian formulation (Kreuzer & Kasess, 2015). The advantage is that both the frequency and bandwidth of each vocal tract resonance enter into the calculation which may be particularly useful for enhancing modification of tract configurations that include branching into the nasal passages or subglottal airways.…”
Section: Methodsmentioning
confidence: 99%
“…Carré’s work focused on how perturbations of a uniform tubular conduit seem to give rise to the vocal tract shapes observed in speech articulation, whereas the goal in Story (2006) was in tuning measured vocal tract shapes such that their calculated resonance frequencies better matched the formant frequencies obtained from analysis of recorded speech. Adachi et al (2007) and Kreuzer and Kasess (2015) formulated a similar iterative approaches but added the effects of vocal tract length perturbation and nasal branching, respectively, to the calculation of acoustic sensitivity functions.…”
Section: Introductionmentioning
confidence: 99%